INFLUENCE OF TYPE OF WHELPING ON NEONATAL MORTALITY IN PUPS - SUBRAMANI, A; ARUNMOZHI, N; SRIDEVI, P; SHAFIUZAMA, M (The Indian Journal of Animal Reproduction, 2022)
The puppies (n=100) born to bitches that underwent Spontaneous Whelping (SW), Assisted Whelping (AW) and Caesarean section (CS) were divided into groups as SW (n=30), AW (n=35) and CS (n=35). Out of 100 puppies, 25% were born dead (2% SW, 7% AW and 16% CS). Among viable pups at birth, the early neonatal mortality till 24 h was 18% (0% SW, 5.7% AW and 45.7% CS). In brief, the stillbirth and early neonatal mortality was high in pups delivered through caesarean compared to spontaneous or assisted whelping.